Application of Coupled Optoelectronic Oscillator on Optical Sampling. (2016) - Jiang, Fan; Lam, Huy Quoc; Zhou, Junqiang; Zhang, Hailiang; Shum, Perry Ping; Zhang, Xinliang
Abstract: A coupled optoelectronic oscillator (COEO) with a polarization-maintaining-fiber based laser cavity is constructed and demonstrated. The mode-locking process and the interaction between the intra cavity power and dispersion is investigated to stabilize and optimize the system. This standalone signal source is capable of outputting pure 10.1 GHz RF signal as well as stable ultrashort optical pulses at corresponding repetition rate simultaneously. The phase noise of the 10.1 GHz RF signal is measured to be as low as -133.25 dBc/Hz at 10 kHz offset frequency. With its dual output of self-synchronized high-quality RF carrier and optical pulses, such a signal generator could be applied as the pulse and clock source in a high speed photonic assisted sampling analog-to-digital converter (ADC) and improve the system performance.